The Channel Branches & Network Vessels on the Tianhui Lacquered Meridian Figurine—Taking the Heart-Regulated Channel as an Example - Qi ZHOU; Lena Springer; Jin LU (Chinese Medicine and Culture)
Abstract. Along with the surge of unearthed medical literature and cultural relics in recent years, a network of channels in the system of medical conduit vessels (meridians) during the early Western Han dynasty has become much clearer gradually. In it, the increasing number of channel branches, network vessels and needle insertion holes (acupoints) is an important feature of the development of channel medicine during the Western Han dynasty. This is not only a reflection of the expanding requirements of the theoretical system of the main trunk channels and other vessels, but also an inevitable result of the continuous enrichment and accumulation of clinical experience. This article integrates the information about channel branches, network vessels, inscriptions, dots and further relics on the Tianhui (天回) Lacquered Meridian Figurine to compare the unearthed literature of the channel genre with the transmitted classical literature about acupuncture. The “Heart-Regulated Channel” in Medical Manuscripts on Bamboo Slips from Tianhui (《天回医简》) serves as an example to explain the occurrence, development and changes of the channel branches and network vessels in the early system of medical channels.